Islamic Spirituality (ROHIS) and Its Effect on Establishment of Character and Religious Attitude of Students: Study Of SMA Negeri 1 Kotamobagu , North Sulawesi - Massi, Moh Rafit; Zaenuri , Ahmad (Pekerti: Journal Pendidikan Islam dan Budi Pekerti, 2022)
This study aims to determine the effect of active participation in Islamic Spirituality extracurricular activities (ROHIS) on the formation of students' character. Furthermore, the shape of the character will be included in the typology of religious attitudes and the direction of the trend will be seen. By using the type of Field Research and a mix method approach between the Qualitative Method and the Quantitative Method, the authors suspect that there is a significant influence between the activity of participating in extra-curricular activities of Islamic Spirituality on the formation of the character of students. Furthermore, if grouped in the typology of religious attitudes, students who actively participate in Islamic Spirituality extra-curricular activities have a tendency to Inclusive-Formalistic diversity attitudes. In social attitudes towards each other they tend to be inclusive, but in religious practice they tend to emphasize formalistic religious rites and have not emphasized the substance aspect